“Because he was disgusting”: transforming relations through positioning in messenger-supported group psychotherapy - Kabatnik, Susanne (Frontiers in Psychology, 2024)
This article deals with positioning in messenger-supported group psychotherapy in terms of transforming relations. The aim of the messenger-supported therapy format is to work through conflicts that have arisen with people via messenger services. This is achieved in different phases of conversation, such as describing the situation, analysing one's own behaviour and defining wishes, by collaboratively drafting a message to the person from the conflict. Using a case study, I show how the interactants work through a conflict through positioning, constitute group identity and relationships and thus also transform their stance concerning the issue. Moreover, positioning serves the collaborative formulation of a message and thus also the change of the relationship to the person from the messenger communication.1 I would like to express my sincere gratitude to Prof. Dr. Frank Padberg's team at LMU Munich and especially to Dr. rer. nat. Fabienne Große Wentrup for numerous inspiring discussions and as well as the always excellent cooperation.